Assessment of clinical profile of patients with non-radiographic axial spondyloarthropathy in a tertiary health-care center - Limaye, Saurabh; More, Shraddha; Nadkar, Milind; Mulkalwar, Alhad; Haider, Hunaid; Jaju, Sujay (Asian Journal of Medical Sciences, 2022)
Background: Axial spondyloarthritis (nr-axSpA) is an inflammatory and immune-mediated condition comprising clinically differentiated ankylosing spondylitis (AS) and nonradiographic nr- axSpA. Clinically, as the name suggests, non-radiographic nr- axSpA has an absence of definitive plain X-ray evidence of structural damage to the sacroiliac joint. Aims and Objectives: The aim of the study was to assess and evaluate the clinical profile of patients with non-radiographic axial spondyloarthropathy. Materials and Methods: This study was conducted in the department of Medicine over 18 months in a tertiary health care institution, being a prospective and observational type done with 43 subjects. Results: We observed a major improvement as per ASDAS criteria present among 53.49% of subjects, followed by clinically significant improvement among 27.91% of subjects. About 18.60% of subjects did not show any improvement. About 9.3% of subjects showed radiological progression. Out of eight cases that did not show improvement, all presented with low back pain and morning stiffness. About 62.5% had peripheral arthritis. About 87.5% had Schober’s test positive, FABER test (62.50%) and sacroiliac joint tenderness found among 7.5% of subjects. A total of 4 (9.3%) patients showed radiological progression. All of them have low back ache and morning stiffness, and three of them having peripheral arthritis at presentation. We found that patients who showed progression had higher mean ESR and CRP (45 and 36.5, respectively) values and a very high disease activity as per ASDAS and BASDAI criteria. Conclusion: There is a great scope and need for research to differentiate the magnetic resonance imaging (MRI) changes in the normal population against the ones patients with spinal diseases to be able to use MRI with precision in patients with non-radiographic axial spondyloarthropathy (nr-axSpA). As assessed, currently physiotherapy and NSAIDS are first line therapy for patients suffering from non-radiographic axial spondyloarthropathy.